Exercise induced bronchoconstriction in elite athletes: measuring the fall - Holzer, K.; Douglass, J. A. (Thorax, 2006)
Decreased FEV1 in response to bronchial provocation challenge remains the method of choice for diagnosing EIB in elite athletes, but the exact level of fall which represents an abnormal response still needs to be determined